Decrease in Cytotoxicity of Copper-Based Intrauterine Devices (IUD) Pretreated with 6-Mercaptopurine and Pterin as Biocompatible Corrosion Inhibitors - Alvarez, Florencia (2013)
The copper intrauterine device (IUD) based its contraceptive action on the release of cupric ions from a copper wire. Immediately after the insertion, a burst release of copper ions occurs, which may be associated to a variety of side effects. 6-Mercaptopurine (6-MP) and pterin (PT) have been proposed as corrosion inhibitors to reduce this harmful release. Pretreatments with 1x10-4 M 6-MP and 1x10-4 M PT solutions with 1h and 3h immersion times were tested. Conventional electrochemical techniques, EDX and XPS analysis, and cytotoxicity assays with HeLa cell line were employed to investigate the corrosion behavior and biocompatibility of copper with and without treatments. Results showed that copper samples treated with PT and 6-MP solutions for 3 and 1 h, respectively, are more biocompatible than those without treatment. Besides, the treatment reduces the burst release effect of copper in simulated uterine solutions during the first week after the insertion. It was concluded that PT and 6-MP treatments are promising strategies able to reduce the side effects related to the "burst release" of copper-based IUD without altering the contraceptive action.